An analysis of job satisfaction as mediator to employee retention at bank employee - Dini, Yuli Indah Fajar; Kurniawan, Eugene (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
This study analyzes the effects of work environment, job security, and transformational leadership on employee retention, with job satisfaction as a mediating variable among Bank Perkreditan Rakyat (BPR) employees in Batam City. This quantitative study involved 205 BPR employees in Batam City. Data were collected through Google Forms questionnaires and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 3.0 software. Findings indicate that work environment, job security, and transformational leadership positively influence job satisfaction. This elevated job satisfaction subsequently enhances employee retention, confirming the mediating role of job satisfaction in these relationships. This research contributes novel insights by empirically testing the mediating role of job satisfaction in the banking context, which faces high turnover rates and unique organizational pressures. The findings offer practical implications for human resources management in the financial sector to design more effective employee retention strategies.